PROTECTING MINORITIES ACCORDING TO THE UNITED NATIONS CONVENTION FOR THE PROTECTION OF HUMAN RIGHTS - Ahmed Saleem Janabi (Scholar Express Journal, 2022)
In every society there exist individuals who belong to a minority because of his or her ethnic, religious, linguistic or cultural particularities that divert from the majority population. These particularities easily place the individuals into an unequal or even discriminatory position in the society. The minorities can therefore be considered to belong to vulnerable groups, although this is not always the case
Keywords: ethnic; religious; linguistic or cultural particularities